2020
DOI: 10.7150/thno.48264
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circPPM1F modulates M1 macrophage activation and pancreatic islet inflammation in type 1 diabetes mellitus

Abstract: Rationale: Macrophages play critical roles in the pathogenesis of type 1 diabetes mellitus (T1DM). Circular RNAs (circRNAs) are a novel class of endogenous RNAs with covalently closed loop structures, implicated in various disease processes. However, their impact on macrophage activation and T1DM pathogenesis remains elusive. Methods: circRNA expression profiles of peripheral blood mononuclear cells (PBMCs) from T1DM children were determined by whole transcriptome microarray.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 49 publications
3
88
0
Order By: Relevance
“…For example, discoveries could convert a simple tumor suppressor into a juggling tumor suppressor depending on the new findings about the functional role of ncRNAs. However, no reported studies were found yet in the literature that demonstrated the role of other ncRNAs (excluding miRNAs and lncRNAs) in regulating macrophagic polarization in different cancers, although few ones are related to non-cancer diseases [ 131 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, discoveries could convert a simple tumor suppressor into a juggling tumor suppressor depending on the new findings about the functional role of ncRNAs. However, no reported studies were found yet in the literature that demonstrated the role of other ncRNAs (excluding miRNAs and lncRNAs) in regulating macrophagic polarization in different cancers, although few ones are related to non-cancer diseases [ 131 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of circHIPK3 and ciRS-7/CDR1as in the islets of wild type animals resulted in impaired insulin secretion, reduced β -cell proliferation, and survival [ 12 ]. Circular RNA circPPM1F modulates M1 macrophage activation and pancreatic islet inflammation in type 1 diabetes [ 34 ]. Circulating circular RNA profiles have also been reported to be associated with type 1 diabetes [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…One is the circRNA, lncRNA, and mRNA expression profile GSE133225, and the other one is the miRNA expression profile GSE133217. Both expression profiles were provided by Zhang Caiyan and Zhou Yufeng, 25 , 36 and included 4 peripheral blood mononuclear cells (PBMCs) samples from T1DM patients and 4 PBMCs samples from healthy volunteers.…”
Section: Methodsmentioning
confidence: 99%
“… 24 Another study by Zhang et al found that circRNA circPPM1F modulates M1 macrophage activation and pancreatic islet inflammation in T1DM. 25 Therefore, examining the expression of lncRNAs and circRNAs and exploring their underlying mechanism in T1DM opens avenues to a better understanding of the T1DM pathogenesis.…”
Section: Introductionmentioning
confidence: 99%